Effect of animal waste and vegetable compost on production and growth of earthworm (Eisenia fetida) during vermiculture - D. S. J. V. Vodounnou; D. N. S. Kpogue; C. E. Tossavi; G. A. Mennsah; E. D. Fiogbe (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The purpose of the study is to evaluate the effect of different animal product wastes and plant compost on survival and growth of earthworm (Eisenia fetida). Methods The study is realized in a vermibin for a duration of 90 days. The initial physico-chemical parameters (pH, humidity, ash, organic matter, carbon, nitrogen, phosphorus and C:N ratio) were determined in each waste of the different substrates before the study. Six waste products (pig, poultry, rabbit, cattle, sheep and vegetal compost) in triplicate (6 9 3) were used for earthworm production. In each 12-l content vermibin, 2 kg of substrate and 30 g of mature earthworms were sown. Each month, the growth control was realized by earthworms harvest and weighing. The earthworms were put back in substrate in vermibin and 500 g of substrate were completed. The pH was measured every week. Results The physico-chemical parameters (pH, ash, organic matter, carbon, phosphorus, nitrogen and C:N ratio) varied (P.05) according to different substrate. The C:N ratio of different organic substrates are in the range of 8.46 in vegetable compost to 19.39 in pig dung. At the end of study the biomass gain and mortality varied (P.05) according to different treatments. The growth rate varied according to different organic waste (P.05) and ranged between -0.06 ± 0.02 (vegetable compost) and 1.34 ± 0.11 (cow dung). Maximum weight gain and highest growth rate were attained with cow dung. Earthworm biomass gain in different animal wastes is in the order of: cow [pig[rabbit [poultry[sheep [compost vegetable. Conclusion The animal wastes (cow, sheep, pig, rabbit and poultry) and vegetable compost can be used to produce the earthworm. But the growth and produce depend on the biochemical quality of the substrates and the availability and facility for using a nutritive element.